Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.12944/cwe.5.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Idol immersion and physico-chemical properties of South Gujarat rivers

Abstract: An idol of Lord Ganesh is worshipped with all rituals during this Ganesh-chaturthi. The time span of festival may vary from one and half day to five days, seven days or ten days also and idol are immersed in lotic or lantic water bodies. We have carried out study in South Gujarat where Ganesh idol immersion takes place in huge quantity with full of rejoice, but due to that water quality gets affected at alarming rate. For such pollution effects by idol immersion many researches have done work on the same in In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Bhattacharya et al (2014) reported the effect of idol immersion on hardness (116.33 mg/l pre immersion and 136.74 mg/l during the immersion) in Ganga river which was moderately similar findings of present investigation. Malik et al (2012) also reported high value (347 ppm) of total hardness during immersion period in Tapi River.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Bhattacharya et al (2014) reported the effect of idol immersion on hardness (116.33 mg/l pre immersion and 136.74 mg/l during the immersion) in Ganga river which was moderately similar findings of present investigation. Malik et al (2012) also reported high value (347 ppm) of total hardness during immersion period in Tapi River.…”
Section: Resultsmentioning
confidence: 83%
“…1). The decrease trend in DO was cumulative effect of idol immersion activities (Desai and Tank, 2010, Azahar, 2011 andMalik et al, 2012) in different rivers of southern Gujarat including Tapi. The free CO2 was generated from the microbial activities and it required for the photosynthesis which affect the algal growth.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…in the azo dyes compounds, such as hydroxyl, carboxylic acid, halogens, esters and amines [19,20]. An important uses of azo imidazole compounds used analytical reagents for solvent extraction to determination of some metal ions [21,22].…”
Section: Asian Journal Ofmentioning
confidence: 99%